Ответы и объяснения

2013-02-02T15:43:43+00:00

(4)/(a²-4)-(1)/(a²+4a+4)=(1)/(a-2)

(4)/(a²-4)-(1)/(a+2)²=(1)/(a-2) (приводим к общему знаменателю)

 

(4)/(a-2)(a+2)(a+2)²-(1)/(a+2)²(a+2)(a-2)=(1)/(a-2)(a+2)(a+2)²

(4(a+2)²)-(a²-4)=(a+2)(a+2)³

4*(a+2)²-(a²-4)=(a+2)*(3a+10)

(a+2)*(3a+10)=(a+2)³

1.3a²+10a+6a+20=0 ; по т. виета(обр.) a1+a2=-16/3 ; a1*a2=20/3 ;

a1=-3 целых 1/3 ; a2=-2

2.(a+2)³=0 ; a³+6a²+12a+8=0 ;

(a³+6a²)+(12a+8)=0 ; 

3.a²(a+6)+4(3a+2); (a²+4)=0

или 

(a+6)(3a+2)=0

по т Виета(обр.)

a3+a4=-20/3

a3*a4=4

a3=-6

a4=-2/3

4. (a²+4)=0

a²=-4(невозможно)

Ответ:  -6; -2/3; -2; -3 целых 1/3